2002
DOI: 10.1073/pnas.182199699
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by which 2,2,2-trifluoroethanol/water mixtures stabilize secondary-structure formation in peptides: A molecular dynamics study

Abstract: Molecular dynamics simulation techniques have been used to investigate the effect of 2,2,2-trifluoroethanol (TFE) as a cosolvent on the stability of three different secondary structure-forming peptides: the ␣-helix from Melittin, the three-stranded ␤-sheet peptide Betanova, and the ␤-hairpin 41-56 from the B1 domain of protein G. The peptides were studied in pure water and 30% (vol͞vol) TFE͞water mixtures at 300 K. The simulations suggest that the stabilizing effect of TFE is induced by the preferential aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
462
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(516 citation statements)
references
References 46 publications
49
462
1
4
Order By: Relevance
“…A native-like fold in TFE/water at pH 2 (MD_pH2_TFE) seems to prefer protein-TFE interaction over protein-water interaction as indicated by the peak of the first solvation layer of TFE around 0.5 nm. This is in agreement with results from previous MD simulations of peptides in explicit TFE/water solutions which showed an accumulation of TFE molecules at the peptide surface Roccatano et al 2002;Diaz et al 2002;Mehrnejad et al 2007). At high temperature or with distance restraints applied (MD_pH2_TFE_HT and MD_pH2_TFE_DR) both solvents penetrate the protein.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A native-like fold in TFE/water at pH 2 (MD_pH2_TFE) seems to prefer protein-TFE interaction over protein-water interaction as indicated by the peak of the first solvation layer of TFE around 0.5 nm. This is in agreement with results from previous MD simulations of peptides in explicit TFE/water solutions which showed an accumulation of TFE molecules at the peptide surface Roccatano et al 2002;Diaz et al 2002;Mehrnejad et al 2007). At high temperature or with distance restraints applied (MD_pH2_TFE_HT and MD_pH2_TFE_DR) both solvents penetrate the protein.…”
Section: Discussionsupporting
confidence: 93%
“…Solution X-ray scattering studies suggest that an important factor is the clustering of the alcohol molecules in TFE aqueous solution (Hong et al 1999). NMR data, supported by MD simulations of peptides in explicit TFE/water solutions, show that this clustering results in an accumulation of TFE molecules around the peptide surface Roccatano et al 2002;Diaz et al 2002;Mehrnejad et al 2007). By coating the peptide surface they partially exclude water molecules (Starzyk et al 2005).…”
Section: Introductionmentioning
confidence: 84%
“…5d) (33). In summary, the explanation for both the EPR and CD observations is that TFE provides a low dielectric environment that favors the formation of intrapeptide hydrogen bonds, thus stabilizing the ␣-helix formed by mMBP (83-92) (34).…”
Section: Resultsmentioning
confidence: 90%
“…It has been suggested that this propensity for aggregation may act in coordination with their hydrophobic nature to bind with the hydrophobic residues of proteins (10,34). The hydrophobic aggregates reduce the local polarity surrounding the peptide, resulting in an increase in intramolecular hydrogen bonding (16,35,36). There is, however, limited experimental evidence of direct binding of fluorinated alcohols with hydrophobic residues (22,37).…”
Section: Construction Of Solvation Energy Of Relaxationmentioning
confidence: 99%